Employee Assessment Through Job Satisfaction - Satiandra Putra Dalimunthe, Ferry; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
This research was conducted to examine the influence of competency and motivation on job satisfaction with work discipline as an intervening variable. This type of research uses quantitative, primary data sources as the data source, the collection technique used is quantitative. The population used was 80 employees. The sample used was also 80 employees using a saturated sampling technique. The research model used is method analysis. The results of this research are as follows: Work Discipline has a positive and significant effect on Job Satisfaction with an original sample value of 0.390 and a p value of 0.000 <0.05. Competence has a positive and insignificant effect on Work Discipline with an original sample value of 0.071 and a p value of 0.257 > 0.05. Competency has a positive and significant effect on Job Satisfaction with an original sample value of 0.234 and a p value of 0.001 < 0.05. Motivation has a positive and significant effect on Work Discipline with an original sample value of 0.722 and a p value of 0.000 <0.05. Motivation has a positive and significant effect on Job Satisfaction with an original sample value of 0.377 and a p value of 0.000 <0.05. Competency has an indirect positive and insignificant effect on Job Satisfaction through Work Discipline with an original sample value of 0.028 and a p value of 0.262. Motivation has a positive and significant influence on Job Satisfaction indirectly through Work Discipline with an original sample value of 0.281 and a p value of 0.000.